Butyrate protects against high‐fat diet‐induced atherosclerosis via up‐regulating ABCA1 expression in apolipoprotein E‐deficiency mice. (12th February 2020) - Du, Yu; Li, Xingxing; Su, Chunyan; Xi, Mei; Zhang, Xiumin; Jiang, Zhibo; Wang, Li; Hong, Bin
Abstract : Background and Purpose: The gut microbial metabolite butyrate is linked to the modulation of metabolic disease. The mechanism by which butyrate effects in atherosclerosis is unknown. Hence, the present investigation into effects of butyrate on high‐fat diet‐fed ApoE −/− mice after 16 weeks' administration. Experimental Approach: Gut microbiota composition was analysed via 16S rRNA gene sequencing of caecal contents. The effects of butyrate on atherosclerosis were evaluated in vivo using the ApoE −/− mice model. Serum lipids and glucose were analysed for physiological changes and differentially expressed genes in liver samples were identified by hepatic transcriptome profiling. The proteins involved in reverse cholesterol transport were quantified by Western blot and immunohistochemical staining. Finally, the up‐regulatory effects of butyrate on ATP‐binding cassette sub‐family A member 1 (ABCA1) were further evaluated in RAW 264.7 cells along with role of specificity protein 1 by inhibition and silencing. Key Results: Oral gavage of butyrate altered microbiota composition and enhanced gut microbial diversity that was decreased by high fat diet (HFD). Butyrate treatment significantly inhibited the HFD‐induced atherosclerosis as well as hepatic steatosis without changing body weight gain in ApoE −/− mice. Butyrate had metabolic effects on the liver by regulation of gene expression involved in lipid/glucose metabolism. Furthermore, ABCA1 was significantly induced by butyrate in vivo, ex vivo and in vitro and Sp1 pathway was identified as a potential mechanism. Conclusion and Implications: Butyrate ameliorates HFD‐induced atherosclerosis in ApoE −/− mice via ABCA1‐mediated cholesterol efflux in macrophages, which suggesting a promising therapeutic strategy for protecting against atherosclerosis. Abstract :